Social Yet Creative: The Role Of Social Relationships In Facilitating Individual Creativity - Perry-Smith, Jill E. (Academy of Management Journal, 2006)
Integrating creativity and social network theories, I explore the direct and interactive effects of relationship strength, network position, and external ties on individual creative contributions. Results from a study of research scientists suggest that weaker ties are generally beneficial for creativity, whereas stronger ties have neutral effects. I also found that centrality is more positively associated with creativity when individuals have few ties outside of their organization and that the combination of centrality and many outside ties is not optimal. I discuss the implications of these findings for creativity and social network research.